Современный статус баклана большого на внутренних водоемах Украины - Бондарчук, Ю.М.; Пшеничный, С.В.; Каминская, Н.В.; Панчук, А.С.; Давыденко, И.В.; Серебряков, В.В. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
From the second half of the XIX century to the beginning of the XX century the Cormorant was known in the Ukraine as breeding and wintering species of the sea coasts. During the last century and at the beginning of the current century its status changes relative to the territory: the Cormorant spread over the whole Ukraine and became numerous species in the most suitable inland waters. Distribution of these populations is discussed on the bases of the available own and published data analysis.